-5(x+2)=x-2+2(2x+2)

Simple and best practice solution for -5(x+2)=x-2+2(2x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+2)=x-2+2(2x+2) equation:


Simplifying
-5(x + 2) = x + -2 + 2(2x + 2)

Reorder the terms:
-5(2 + x) = x + -2 + 2(2x + 2)
(2 * -5 + x * -5) = x + -2 + 2(2x + 2)
(-10 + -5x) = x + -2 + 2(2x + 2)

Reorder the terms:
-10 + -5x = x + -2 + 2(2 + 2x)
-10 + -5x = x + -2 + (2 * 2 + 2x * 2)
-10 + -5x = x + -2 + (4 + 4x)

Reorder the terms:
-10 + -5x = -2 + 4 + x + 4x

Combine like terms: -2 + 4 = 2
-10 + -5x = 2 + x + 4x

Combine like terms: x + 4x = 5x
-10 + -5x = 2 + 5x

Solving
-10 + -5x = 2 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-10 + -5x + -5x = 2 + 5x + -5x

Combine like terms: -5x + -5x = -10x
-10 + -10x = 2 + 5x + -5x

Combine like terms: 5x + -5x = 0
-10 + -10x = 2 + 0
-10 + -10x = 2

Add '10' to each side of the equation.
-10 + 10 + -10x = 2 + 10

Combine like terms: -10 + 10 = 0
0 + -10x = 2 + 10
-10x = 2 + 10

Combine like terms: 2 + 10 = 12
-10x = 12

Divide each side by '-10'.
x = -1.2

Simplifying
x = -1.2

See similar equations:

| 3(n-15)+8=11 | | (H^2+4h-4)+(5h^2-8h+2)=6h^2-4h-2 | | 1/4+w=6 | | ax+6=(x+3) | | 2w+2l=l | | -16x^2+8x+190=0 | | 1/4+w=61/3 | | -6(x+2)-11=21+4 | | -3(y+5)=15 | | 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p | | 0.09xX=110.30 | | X+(x-1)=2(x+3) | | 12x-2m= | | 3x4/9= | | -5x+2(4x-15)=-63 | | -3(-7w+4)-3w=4(w-5)-4 | | W=1000-0.2t | | 28a^3b^4+20a^2b^2-16ab^3= | | x^8=140 | | 40x-40=28 | | 67+4y-30=15y-12-4y | | 9+3y-3=7y+15-3y | | 8x+3y=67 | | 8x-5y=-9 | | 18+-9= | | V(w-l)=p | | 93-(7x+6)=7(x+6)+x | | 2x^2+14x+59=0 | | Ab+c=2 |

Equations solver categories